Three is equal to four

16 юли 2009

Theorem: 3=4

Proof:

Suppose:
a + b = c

This can also be written as:
4a – 3a + 4b – 3b = 4c – 3c

After reorganizing:
4a + 4b – 4c = 3a + 3b – 3c

Take the constants out of the brackets:
4 * (a+b-c) = 3 * (a+b-c)

Remove the same term left and right:
4 = 3






Драсни коментарче по темата (ако може на кирилица, благодаря за което)

   


:bye: 
:good: 
:negative: 
:scratch: 
:wacko: 
:yahoo: 
B-) 
:heart: 
:rose: 
:-) 
:whistle: 
:yes: 
:cry: 
:mail: 
:-( 
:unsure: 
;-)